Um modelo matemático para estimar o risco de desenvolver câncer de pulmão por meio de sistemas fuzzy - Laghetto, Beatriz Krabbe (Universidade Federal de São Carlos, 2016)
The main aims of this work are to study the ways to model mathematically uncertainties using Fuzzy Sets Theory, and then propose a mathematical model to estimate the risk of an individual developing lung cancer through a system based rule fuzzy. Therefore, we consider risk factors, namely smoking, pollution, history of lung disease, family history and contact with chemical agents such as system input variables fuzzy. Lung cancer is a disease that has no symptoms in its early stages, making the diagnosis more difficult to be done and, therefore, most discovered when the cancer is already advanced. This type of cancer is highly lethal and frequent in the population, an increase of 2 % per year in its worldwide incidence.
Keywords: Modelo matemático; Conjuntos fuzzy; Método de inferência de mamdani; Câncer de pulmão; Fatores de risco; Mathematical modeling; Fuzzy Sets; Mamdani’s Inference Method; Lung cancer; Risk factors; Medicine; CIENCIAS EXATAS E DA TERRA::MATEMATICA